Existence of positive solution for a fractional order nonlinear differential system involving a changing sign perturbation - He, J.; Zhang, Xinguang; Wu, Yong Hong (Shomal University, 2016)
In this paper, we study a class of singular fractional order differential system with a changing-sign perturbation which arises from fiuid dynamics, biological models, electrical networks with uncertain physical parameters and parametrical variations in time. Under suitable growth condition, the singular changing-sign system is transformed to an approximately singular fractional order differential system with positive nonlinear term, then the existence of positive solution is established by using the known fixed point theorem.